Clinical and economic impact of treated CMV infection in adult CMV‐seropositive patients after allogeneic hematopoietic cell transplantation. Issue 12 (29th June 2020) - Peffault De Latour, Régis; Chevallier, Patrice; Blaise, Didier; Alami, Sarah; Lévy‐Bachelot, Laurie; Allavoine, Thierry; Tadmouri, Abir; Blomkvist, Josefin; Duhamel, Alain; Srour, Micha; Beauvais, David; Yakoub‐Agha, Ibrahim
Abstract: Objective: Recipients of allogeneic hematopoietic stem cell transplantation (allo‐HCT) with positive cytomegalovirus (CMV) serology are at increased risk of morbidity and mortality. The primary objective of this study was to assess the association between treated CMV infection and overall mortality within 1 year after allo‐HCT in adult CMV‐seropositive Recipients (R+). Secondary objectives included overall 5‐year mortality after allo‐HCT, risk factors for treated CMV infection, associations between treated CMV infection and allo‐HCT complications and medical costs. Methods: A multicenter retrospective cohort study was conducted in adult CMV‐seropositive recipients (R+) who underwent to allo‐HCT between 1st January 2010 and 31st December 2014. Results: Five hundred seventy two CMV‐seropositive patients (mean age, 50.2 years) undergoing allo‐HCT between 2010 and 2014 were included; 55.9% of donors were CMV seropositive. CMV infection treated with antiviral therapy was reported in 227 patients (39.7%) after transplantation. One‐year overall mortality was significantly increased in patients with treated CMV infections (hazard ratio, 1.86; 95% CI, 1.16‐3.00; P  = .011). Mean medical costs during the first post‐HCT year were higher in patients with CMV infection (€46 853 vs €31 318; P  < .0001). Conclusion: In this large cohort of CMV‐seropositive patients undergoing allo‐HCT, treated CMV infection was significantly associated with an increased 1‐year risk of overall mortality, with increased length of stay and with hospitalization cost. The burden of CMV disease in allo‐HCT could be reduced in the future by appropriate prophylactic strategies.